Natural Products in the Management of Obesity - Davkova, Iskra; Zhivikj, Zoran; Kukić-Marković, Jelena; Cvetkovik Karanfilova, Ivana; Stefkov, Gjoshe; Kulevanova, Svetlana; Karapandzova, Marija (Archives of Pharmacy, 2024)
Treating overweight and obesity with medications generally offers initial advantages but can result in weight regain after stopping the drugs, as well as in medication-related side effects, and the potential for substance misuse. The allure of herbal products lies in their natural origin, thus leading individuals towards these products in search of a healthier and more sustainable approach to weight loss. Understanding how herbal products interact with biological systems is crucial for assessing their therapeutic potential. Anti-obesity herbal products and their compounds can act through different mechanisms, such as: appetite suppression, digestion and absorption blocking, stimulation of thermogenesis, inhibition of adipogenesis, and modulation of these processes through gene expression. The physiological effects and therapeutic properties exhibited by herbal products are ascribed to the presence and activity of their active components, such as polyphenols, tannins, flavonoids, anthocyanins, stanols, sterols and alkaloids. Furthermore, the synergistic effects of various phytochemicals have been explored to enhance their anti-obesity properties.